PENGUKURAN KINERJA RANTAI PASOK PADA PRODUK KAYU LAPIS (PLYWOOD) DI PT. SAMBAS ALAM LESTARI - YUNI YUNI; Novira Kusrini; Adi Suyatno (Fakultas Pertanian Universitas Tanjungpura, 2019)
The supply chain flow has a very important role, starting from the supply of raw materials to finished products. Therefore, this analysis conducted to measure and assess the implementation of the company's supply chain has been achieved. The aim of this study is to measure supply chain implementation. Supply chain implementation measurement is based on five core processes in the SCOR method. Then the weighting was done using Analytic Hierarchy Process (AHP) for each perspective, dimension, and KPI as well as scoring systems using OMAX and analysis with Traffic Light System. The results showed that the supply chain implementation categorized of green was amount 23 KPIs, yellow categories were 14 KPIs and red categories were 4 KPIs. Scoring results using the OMAX method obtained a total index value of 7,677. Based on the Traffic Light System, the index value is in the yellow category which shows the company’s implementation is close to the target set by the company. It is expected that the company can maintain good implementation indicators and can improve implementation indicators that near targets and poor implementation indicators, in order to be better in accordance with the company’s goals in the future.The supply chain flow has a very important role, starting from the supply of raw materials to finished products. Therefore, this analysis conducted to measure and assess the implementation of the company's supply chain has been achieved. The aim of this study is to measure supply chain implementation. Supply chain implementation measurement is based on five core processes in the SCOR method. Then the weighting was done using Analytic Hierarchy Process (AHP) for each perspective, dimension, and KPI as well as scoring systems using OMAX and analysis with Traffic Light System. The results showed that the supply chain implementation categorized of green was amount 23 KPIs, yellow categories were 14 KPIs and red categories were 4 KPIs. Scoring results using the OMAX method obtained a total index value of 7,677. Based on the Traffic Light System, the index value is in the yellow category which shows the company’s implementation is close to the target set by the company. It is expected that the company can maintain good implementation indicators and can improve implementation indicators that near targets and poor implementation indicators, in order to be better in accordance with the company’s goals in the future.